Impact of chemotherapy on hippocampal neurogenesis and potential protective strategies - Lasio, Valeria (2017)
Background and objectives: An increasing number of cancer patients have described experiencing cognitive dysfunctions which are associated with their chemotherapy treatment. This has been called “chemobrain” in patient forums and articles. It has been shown in animal models treated with a range of chemotherapy agents that chemotherapy induces cognitive deficits and a decrease in hippocampal neurogenesis. Antidepressants, anti-inflammatory drugs and physical activity have been proposed to counteract the effect of chemotherapy and provide protection against cognitive impairment associated with cancer treatments. This thesis has used in vivo studies, in rats and Sox1-GFP transgenic mice to firstly evaluate the effect of acute and chronic 5-Fluoruracil (5-FU) treatment on different subpopulations of neural stem cells in the hippocampus. Secondly, the effect of prior treatment with the antidepressant fluoxetine and the anti-inflammatory indomethacin on the impact of chronic treatment with chemotherapy was measured in terms of their effect on cell proliferation, inflammation and DNA damage. The effect of prior physical exercise on acute treatment with 5-Fluoruracil was measured in terms of cell proliferation and differentiation. Methods: Animals were administrated either acute (single injection) or chronic (4 to 6 injections) of 5-FU with or without fluoxetine and indomethacin or physical exercise. Cell proliferation (Ki67), early neural differentiation (DCX), neural stem cells markers (GFAP, Sox1), inflammation (Iba1, Cox2) and DNA damage (γ-H2AX) were quantified by immunostaining either 24hr or 1 week after the last injection of chemotherapy. Morphological studies, to differentiate different stages of neural stem cells development and the state of microglia activation were conducted using confocal imaging. 3 Results: Acute treatment of Sox1-GFP mice with 5-FU caused a decrease in cell proliferation while chronic treatment induced a depletion of the neural stem cell pool and a reduction of the number of microglia. Prior chronic treatment with indomethacin did not prevent the decrease in the number of neural stem cells but did prevent the decline in cell proliferation and microglia. Rats chronically injected with chemotherapy and allowed to recover for 1 week, showed a decreased proliferation and number of microglia, an increased microglia activation, Cox-2 expression and DNA damage. Prior chronic treatment with fluoxetine prevent the decrease in proliferation and number of microglia, the increased microglia activation and DNA damage. Prior treatment with fluoxetine and indomethacin prevented these effects. Physical exercise prior to acute treatment with 5-FU enhanced the overall amount of neurogenesis but, possibly, due to a low dose of chemotherapy it was not possible see a significant effect of the chemotherapy. Conclusions: The chemotherapy agent 5-FU affected the neural stem cell pool and the number of proliferating cells in the hippocampus. Chronic administration with fluoxetine can prevent the decrease in the number of proliferating cells, microglia activation and DNA damage while treatment with Indomethacin protects only against the effect of 5-FU on proliferating cells and microglia activation.